Effect of Surface Roughness of Charge Hole on Detonation - Fumihiko Sumiya; Yoshikazu Hirosaki; Yukio Katoh; Yuji Wada; Yuji Ogata; Kunihisa Katsuyama (International Society of Explosives Engineers, 1996)
In our previous work, the results of photographic observation using a high speed framing camera showed that the difference between precursor air shock wave velocity and detonation velocity was primary factor for the channel effect. It is assumed that the decreasing precursor air shock wave velocity can prevent the channel effect in charge hole.